In vivo visualization of tau deposits in corticobasal syndrome by 18F-THK5351 PET. (29th November 2016) - Kikuchi, Akio; Okamura, Nobuyuki; Hasegawa, Takafumi; Harada, Ryuichi; Watanuki, Shoichi; Funaki, Yoshihito; Hiraoka, Kotaro; Baba, Toru; Sugeno, Naoto; Oshima, Ryuji; Yoshida, Shun; Kobayashi, Junpei; et al.
Abstract : Objective: To determine whether 18 F-THK5351 PET can be used to visualize tau deposits in brain lesions in live patients with corticobasal syndrome (CBS). Methods: We evaluated the in vitro binding of 3 H-THK5351 in postmortem brain tissues from a patient with corticobasal degeneration (CBD). In clinical PET studies, 18 F-THK5351 retention in 5 patients with CBS was compared to that in 8 age-matched normal controls and 8 patients with Alzheimer disease (AD). Results: 3 H-THK5351 was able to bind to tau deposits in the postmortem brain with CBD. In clinical PET studies, the 5 patients with CBS showed significantly higher 18 F-THK5351 retention in the frontal, parietal, and globus pallidus than the 8 age-matched normal controls and patients with AD. Higher 18 F-THK5351 retention was observed contralaterally to the side associated with greater cortical dysfunction and parkinsonism. Conclusions: 18 F-THK5351 PET demonstrated high tracer signal in sites susceptible to tau deposition in patients with CBS. 18 F-THK5351 should be considered as a promising candidate radiotracer for the in vivo imaging of tau deposits in CBS.